Leadership and “Followership”: Do Department Chairs Actually Have “Followers”? - Jeff Buller (Academic Chairpersons Conference Proceedings, 2023)
There is a paradox in higher education: Everyone agrees that good, creative leadership is essential … but no one wants to be led. Most books on leadership or management discuss a leader's "followers" or use some other expression (such as team members, direct reports, or associates) that appears to suggest a different sort of relationship but, when examined carefully, is really just a euphemism for followers. The chair role in higher education is distinctive, however, in that, although it includes supervisory aspects, the members of our departments are also our colleagues. So, how do you lead when you don't really have followers?
Keywords: leadership; followership; management; progress; effective